Xoryp_08180 of Xanthomonas oryzae pv. oryzicola, Encoding a Hypothetical Protein, is Regulated by HrpG and HrpX and Required for Full Virulence in Rice - Yi-ping SHEN; Li-fang ZOU; Yu-rong LI; Hua-song ZOU; Xi-ling LIU; Gong-you CHEN (Journal of Integrative Agriculture, 2012)
Xanthomonas oryzae pv. oryzicola (Xoc) causes a destructive bacterial leaf streak disease in rice. Some of the gene products annotated as hypothetical proteins in the genome of Xoc may contribute to its virulence in rice. A mutant, Mxoc1679, screened from our previous Tn5-tagged mutant library for Xoc strain RS105, showed reduced virulence in rice. In this mutant, a gene named as Xoryp_08180 was disrupted by Tn5 insertion. Xoryp_08180 encodes a 1 306-aa hypothetical protein which is highly conserved in Xanthomonas spp. Non-polar mutation of Xoryp_08180 in RS105 strain led to a significant reduction in bacterial virulence and growth in rice, a delayed hypersensitive response (HR) in non-host tobacco, and a decrease in extracellular protease activity. The deficiencies above were restored to wild-type level in the complementary strain by expressing Xoryp_08180 in trans. In addition, the expression of Xoryp_08180 was repressed in hrpG and hrpX mutants in planta but not in a nutrient-rich condition. These results suggested that Xoryp_08180 is a virulence factor required for extracellular protease production, HR induction and full virulence of Xoc.